Integrasi Pengajaran Interaktif Melalui Inovasi Pembelajaran Dalam Meningkatkan Minat Belajar Siswa - Komala Sari, Lulu; Komalasari, Ratna; Faisal Hakim, Muhammad; Firmansyah, Ridwan; Asiah, Siti (Universitas Majalengka, 2024)
This study aims to explore the integration of interactive teaching through learning innovations at SMKN 1 Cikarang Barat as an effort to enhance students' learning interest. The background of the research indicates that conventional teaching methods, which are still dominant, such as lectures, are ineffective in increasing student engagement. Therefore, interactive teaching that utilizes technology, such as Google Slides and Google Forms, is expected to create a more engaging and enjoyable learning environment. This study also identifies the challenges faced, including resource limitations, differences in perceptions between teachers and students regarding character education, and the need for support from parents and the community. Using a qualitative approach, this research collects data through interviews and observations to understand the views of teachers and students regarding character education and interactive teaching. The results of this study are expected to provide broader insights into the effective implementation of learning innovations that support the character development of students at SMKN 1 Cikarang Barat.